PROCESSOS EDUCATIVOS DAS MULHERES QUILOMBOLAS DE CANDÓI, PARANÁ - BARBOSA, MÔNICA MATOS (2023)
The present research has as field of study the Quilombola Communities of Candói - PR (CRQ): CRQ of Despraiado, CRQ of Vila São Tomé and CRQ of Cavernoso. These communities are made invisible in the municipality, as in the entire state. This practice is based on the pseudo-forgetfulness of black men and women, through racial whitening policies adopted across the country (BATISTELLA, 2012). The objective focuses on the quilombola women of these three communities, we analyze matricentrality as a community and identity value of being a quilombola woman, as an attractor of family and community learning, the blessing and care for herbs, religiosity, ancestral knowledge, care for the family and the link with the association. These events embodied in community practices that organize the educational processes of being a quilombola woman in Candói. Learning is described from the methodological perspective of Learning Constellations, which has been discussed in research by author. Silva (2018). For data analysis, ethnography and its instruments and resources, interviews, observations and notes in the field, questionnaires, document analysis, photos and videos taken between 2018 and 2022 were used. In matricentricity, the feminine is the center of forms of resistance. In this concept, women are at the center of the culture without ruling other members of the community. The Learning Constellation constructed in this work points out perceptible elements in Candói quilombola women: religiosity, ancestral knowledge. They play a key role in maintaining the CRQ's quilombola identity. Five women were protagonists within this research, at CRQ do Despraiado, it was possible to know the story of Dona Cida and Dona Ita, both are guardians of ancestral knowledge in their community. Through their reports it was possible to know the origins of the community and the municipality. At CRQ in Vila São Tomé, we had contact with Dona Neiva, a lady who cultivates African religious traditions, with practices of blessings, teas, bottles. It has been providing services for more than 30 years, free of charge, for those from inside and outside the community, demonstrating the perspective of matricentral generosity, that is, community care. And at CRQ do Cavernoso, we met Dona Marica and Ivanira demonstrating ancestral knowledge; suffering and community care. Ancestry is firmly rooted in CRQ, since everyone descends from Seu Sebastião, a former community leader with enslaved great-grandparents, full of stories to tell, which were passed down by his grandparents and parents. Both women provide care for the bedridden elderly person, in addition to helping with the demands of the community and leading the association. Quilombola women care about their community and follow maternal values to nurture natural, social and cultural life with respect. It is concluded that the quilombola women of Candói are central figures within the community, through their practices of care and knowledge, they fight against dynamics of domination. They assume their history and that of their ancestors, who, despite being socially silenced, are part of Brazil's historical cultural heritage.